An exploration of inservice teachers’ implementation of culturally responsive teaching methods in algebra with African American students - Powell, Tiffany Shamone (Kansas State University, 2009)
Moses & Cobb (2001) argue that algebra is a “civil right” and assert that limited algebraic understanding has an unfavorable impact on African American students’ entry into post-secondary education. Gay (2000) outlines six pedagogical methods, known as culturally responsive teaching (CRT), which emphasize the importance of teachers creating learning environments that relate to the personal experiences and cultural perspectives of minority students. The National Council of Teachers of Mathematics (NCTM) prescribes five process standards (communication, problem solving, connections, representation, and reasoning and proof) and the Equity Principle (includes setting high expectations, responding to the needs of culturally and linguistically diverse students, and providing support) for effective mathematics instruction. CRT, the NCTM Process Standards, and the NCTM Equity Principle served as the conceptual framework for this mixed-method study. Thirty-four teachers from two elementary and two middle schools in one school district in the Midwest responded to The Powell Teaching Mathematics Index (PTMI), a five-option Likert survey that explored teachers’ current “use” and “desire” to use CRT methods, NCTM process standards, NCTM Equity Principle, and teachers’ personal efficacy in learning and teaching mathematics in general and in algebra. Results from the PTMI revealed that teachers had a “desire” to use CRT in mathematics with AA students (M=4.41, SD=0.70); and although there was more variance among respondents, teachers also reported a “desire” to use process standards in algebra with AA students (M=3.94, SD=1.03). One bivariate correlation revealed a relationship between “use” of process standards in general and “efficacy” (r =0.681, p[less than or equal to]0.01). Eight volunteer teachers participated in a professional development workshop on CRT and integrated one of the six pedagogical methods into their classrooms for one month. Teachers reported “strengths” from the implementation phase as: increased student engagement, transition from teacher-directed to student-directed learning and an increase in student confidence in mathematics. Implementation “strains” were reported as: a time consuming process, difficulty in providing individual attention and an increase in classroom noise level. Findings have implications for teacher education programs, local school district and teacher networks.
Keywords: Culturally Responsive Teaching; African American Students; Algebra; Mathematics Education; NCTM Process Standards; NCTM Equity Principle; Education, Mathematics (0280)